Plant impedance spectroscopy: a review of modeling approaches and applications - Van Haeverbeke, Maxime; De Baets, Bernard; Stock, Michiel (Frontiers in Plant Science, 2023)
Electrochemical impedance spectroscopy has emerged over the past decade as an efficient, non-destructive method to investigate various (eco-)physiological and morphological properties of plants. This work reviews the state-of-the-art of impedance spectra modeling for plant applications. In addition to covering the traditional, widely-used representations of electrochemical impedance spectra, we also consider the more recent machine-learning-based approaches.